948 Visceral Artery Aneurysms- A Single Centre Experience Over 6 Years. (4th May 2021) - Zaki, S; Ashrafi, M; Balakrishnan, A
Abstract: Introduction: The incidence of visceral artery aneurysms (VAA) varies from 0.01-0.1%. They are significant with a mortality risk of up to 75% if ruptured. Given there are no national guidelines we decided to conduct this study to assess the management of VAA in our trust and recommend local guidelines. Method: We retrospectively identified patients who had a detected VAA between April 2014 and April 2020. Medical records and relevant imaging were reviewed in detail. MDT outcomes and subsequent mortalities noted. Results: We identified 62 VAA in 59 patients (23 male), median age 65 years, and mean diameter 18.1 mm. 95 % were detected on CT, the indication was mostly malignancy. MDT outcomes were to continue surveillance for 43 patients with yearly scans, 5 patients had primary surgical repair, 7 patients had endovascular interventions, 1 patient had primary endovascular intervention that failed and required surgical intervention. 7 patients were discharged from follow up due to age and size (12 mm) or VAA completely thrombosed. Conclusions: In our unit decisions to intervene were based on size > 20mm, rapid increase in size on surveillance, the presence of portal hypertension or possibly the patients' young age. There were no mortalities linked to VAA.